2015
DOI: 10.1118/1.4932394
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy for stage I seminoma of the testis: Organ equivalent dose to partially in‐field structures and second cancer risk estimates on the basis of a mechanistic, bell‐shaped, and plateau model

Abstract: Radiotherapy for stage I seminoma of the testis may result in an excess risk for the appearance of secondary malignancies in partially in-field organs. The organ- and model-dependent second cancer risk assessments of this study may be of value for patient counseling and follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
0
10
0
1
Order By: Relevance
“…14 Previous studies have already reported large deviations between the mechanistic and bell-shaped models in the estimation of the radiotherapy-induced stomach cancer risk. 21,25 The assessments of the lifetime risks for lung cancer induction following ISRT for mediastinal HL were at least 1.8 times smaller than the baseline risks irrespective of the patient's age and the model used for analyzing the DVH data. The corresponding LARs of breast cancer incidence in females were found to be more than 5.3 times lower.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Previous studies have already reported large deviations between the mechanistic and bell-shaped models in the estimation of the radiotherapy-induced stomach cancer risk. 21,25 The assessments of the lifetime risks for lung cancer induction following ISRT for mediastinal HL were at least 1.8 times smaller than the baseline risks irrespective of the patient's age and the model used for analyzing the DVH data. The corresponding LARs of breast cancer incidence in females were found to be more than 5.3 times lower.…”
Section: Discussionmentioning
confidence: 99%
“…Reported experience suggested that the OED of esophagus used for estimating the relevant carcinogenic effects can be defined by using the model parameters of stomach . Previous studies have already reported large deviations between the mechanistic and bell‐shaped models in the estimation of the radiotherapy‐induced stomach cancer risk …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the more established risk factors for CRC are obesity, old age, physical inactivity, dietary habits, alcohol use, and smoking [10,43]. Cancer treatments such as chemotherapy and radiotherapy have also been implicated in the development of CRC [44][45][46][47][48][49]. These risk factors can also predispose patients to a variety of NCRCs and may explain the commonality among these cancers.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, the main problem arising from the use of IMRT is an increased risk of secondary malignancies [ 24 29 ], and from proton therapy, limited availability of this therapeutic method. So far, we use the above methods in particular clinical situations in patients with GCT.…”
Section: Introductionmentioning
confidence: 99%